Vom Publicum Das Öffentliche in der Kunst - Kammerer, Dietmar (Image, 2014)
In the audience, art and society overlap. It is the place where aesthetic practice becomes public in a society and where political issues in artistic staging become visible and negotiable. This volume poses the question of the aesthetics of the public and the public of the arts. He collects contributions from art history, political philosophy as well as film, theater and media studies and seeks formations of the common in historical and contemporary artistic productions, processes and modes of reception.